Sovietization and desovietization of East and Central Europe's universities - Schacht, Anastassiya (The Routledge handbook of 1989 and the great transformation, 2025)
This chapter studies the Sovietization and subsequent Desovietization of East Central European academia since the late 1940s. These two transformations forced scholars to adjust first to governments’ increased intervention in education, research, and teaching, and then to the sudden disappearance of any such ideological control. Both transformations created a canon of literature inscribing East Central European academia into the role of the disrupted and thus underdeveloped counterpart of its Western peer. The chapter discusses the reasons, plausibility, extent, and limitations of this narrative, arguing for a more nuanced and complex, even if more ambivalent, approach.
Gesehen am 02.02.2026